Photothermal-electrocatalysis interface for fuel-cell grade ammonia harvesting from the environment - Pengfei Wang; Panpan Li; Zhicheng Pan; Kui Liu; Minghao Xie; Liwei Zhou; Min Zhou; Guihua Yu; Zhaoyu Jin (Nature Communications)
Abstract The development of sustainable artificial nitrogen recycling technologies enables ammonia extraction from ambient sources, facilitating zero-carbon Water-Energy-Food (WEF) Nexus integration. While electrochemical reduction of oxidized nitrogen offers promise for ammonia synthesis, purifying low-concentration products remains a challenge, limiting practical applications and undermining the Haber-Bosch process’s viability. Here, we introduce a photothermal-electrocatalysis interface (PTEI) based on a Janus hybrid nanoarchitecture electrode, demonstrating synergistic enhancement in ammonia yield and evaporation performance. The photothermal-electrocatalysis interface-integrated system continuously produces and purifies ~2 M pure ammonia solution at up to 13.7 mg cm−2 h−1 from plasma-ionized air and achieves 80% total nitrogen recovery with 0.36 M ammonia from simulated industrial wastewater. This approach enables efficient extraction of concentrated ammonia for direct fuel cell use, offering techno-economic benefits and significantly reducing global warming impacts via life cycle assessment. Our findings highlight the PTEI system’s innovative potential in addressing WEF Nexus challenges, paving the way for sustainable waste-to-resource/fuel transitions.